"Do riso fez-se o pranto": técnicas de produção do gênero nas notícias de violência em relações afetivas e sexuais do Jornal Pequeno - SILVA, Mayana Helles Nundes da (2014)
Understanding that the media is configured as a technology of gender, ie , as a technology that builds ( s ) gender ( s ) , I argue that the news about violence in affective and sexual relations established by heteronormative subjects that were broadcast by Journal small during the 2000s constitute as statements that articulated with several sets of discourses / knowledges appoint behaviors , gestures and acts that take place in these relationships , the protagonists classify situations and ( re ) produce the binary gender difference itself. In this sense , from the archaeological method and discourse analysis proposed by Michel Foucault , the aim of this study was to search the proved meanings contained in building intelligibility of narratives and discourses realize that present themselves on its banks and how they hang together . The theoretical framework that substantiates my analyzes was chosen to focus the discussions on gender , speech , media , power and violence in emotional and sexual relationships , what made me choose to authors such as Teresa de Lauretis (1987 ) , Joan Scott (1990 ) , Judith Butler (2003 ) , Michel Foucault (2012 ) , Tanya Zimmerman (2012 ) , Barbara Musumeci (1999 ) , among others .